2001
DOI: 10.1364/ol.26.000992
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive monitoring of glucose concentration with optical coherence tomography

Abstract: We have proposed a tested in tissue phantoms and in vivo a novel sensor based on optical coherence tomography (OCT) for noninvasive and continuous monitoring of blood glucose concentration. OCT images were obtained from pig and rabbit skin before and after glucose administration. Slopes of OCT signals decreased substantially (~40% in tissues in vivo) and linearly with the increase of blood glucose concentration from 4 to 30 mM, typical for normal and diabetic subjects. Phantom studies demonstrated 1% accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
159
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(170 citation statements)
references
References 6 publications
3
159
0
5
Order By: Relevance
“…On average, the slope changed 1.9% per 10 mg/dl in these studies. The results of these tests are in good agreement with those obtained in our animal studies (17,18).…”
Section: Analytical Proceduressupporting
confidence: 90%
See 1 more Smart Citation
“…On average, the slope changed 1.9% per 10 mg/dl in these studies. The results of these tests are in good agreement with those obtained in our animal studies (17,18).…”
Section: Analytical Proceduressupporting
confidence: 90%
“…Our previous studies performed in tissue phantoms and animals in vivo with an OCT system showed high accuracy of measurements of changes in the scattering coefficient in tissue phantoms and a good correlation between changes in glucose concentration and the OCT signal slope in animals (17,18). In this pilot study, we tested the feasibility of noninvasive glucose monitoring with this OCT system in healthy human subjects.…”
mentioning
confidence: 94%
“…This is consistent with our study in which collagen solubility predicted glucose to have twice the OCP of glycerol. In addition, it is interesting to note that in efforts to develop non-invasive, optical monitoring of blood glucose levels, a correlation has been reported between a reduction in tissue scattering and glucose concentration [19][20][21]. The reduction in tissue scattering was hypothesized to arise from an increase in glucose concentration in local extracellular space, increasing its refractive index to better match that of tissue scatterers.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of xfOCM should prove useful to monitor changes in beta cell number-for example, during islet regeneration [30] or upon islet transplantation to visualise the islets and their vascularisation in the recipient. Analysing dispersion and spectral absorption characteristics in the sample could add further functional contrast such as variations in metabolite concentrations [31,32]. Eventually, xfOCM could help design new PET and MRI probes that selectively label the pancreatic beta cells and that are necessary for clinical imaging of pancreatic islets by these techniques.…”
Section: Discussionmentioning
confidence: 99%